Knowledge transformation on the economic recovery in post-pandemic - Sri Sarjana; Mahsa Amira Anindya Najib; Innayah Kusuma Dewi; Nur Khayati (Journal of Innovation in Business and Economics, 2021)
Economic recovery is the restoration of the business cycle due to the crisis marked by increased activity in various sectors. Meta-analysis is applied to find novelty through qualitative research development. Knowledge mapping during the pandemic was carried out through an analysis of 995 scientific journals obtained from searches on Google Scholar regarding the concept of economic recovery. This study finds that the scientific evolutionary research found several topics, including privatization, forecast, zakat, adoption, free zone, financing, and pandemic crisis. The novelty of the issues obtained is indicated to have a new value that has the potential to be further developed for the dissemination and diversity of knowledge. Knowledge development on the concept of economic development is expected to improve economic conditions in a business environment experiencing turbulence due to health crises.